Patriots and cosmopolitans : hidden histories of American law - Witt, John Fabian (Harvard University Press, 2007)
Ranging from the founding era to Reconstruction, from the making of the modern state to its post-New Deal limits, John Fabian Witt illuminates the legal and constitutional foundations of American nationhood through the stories of five patriots and critics. In their own way, each of these individuals came up against the power of American national institutions to shape the directions of legal change.